Electroencephalography based brain controlled grasp and lift - Chakraborty, Pritam; Akter, Sanjida; Hasin, Bariyat; Ahmed, Syeda Faria (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2021.